PENGARUH LABEL HALAL DAN KESADARAN HALAL TERHADAP MINAT PEMBELIAN KONSUMEN PADA PRODUK UMKM DI KOTA BIMA - Sri Ernawati; Iwan Koerniawan (STEKOM PRESS, 2023)
The meaning of halal is permissible, while haram is not permissible (prohibited) according to Islamic law. Having a halal certificate can give confidence to companies in using or printing halal labels on product packaging or company premises. This study aims to find out how the influence of the halal label and halal awareness has on the purchase intention MSME products in the Bima City. The type of research used in this study is a type of quantitative research with survey methods. Collecting data by distributing questionnaires with a Likert scale to 100 respondents. Data was processed by statistical analysis using SPSS 20.00. The results showed that the halal label had a positive and significant effect on the intention to purchase MSME products in the Bima City and halal awareness did not have a significant effect on the intention to purchase MSME products in the Bima City. The contribution of this research is hoped that MSME actors will immediately take care of halal certificates so that consumers' interest in buying increases and products can be marketed outside the region so that the wider community can get to know MSME products from Bima city.